Membuat Game Virtual Reality Kota Parepare - Fadil Muslimin, Ahmad; Wahyuddin, Wahyuddin; Nugraha, Wahyu Arta (Jurnal Sintaks Logika, 2024)
Combining virtual reality technology into a game can create a new experience for the player while being able to introduce the icon of Parepare City. Also, in the application, there is a mission or game where in the game there are levels 1 to 4. The purpose of making virtual reality game applications is to help introduce the city of Parepare in a fun way. The experimental method uses a smartphone that already supports the gyroscope sensor, VR Box, or Google Cardboard glasses. The software used in making this game application is Unity, SkecthUp, Visual Studio, and the C# programming language. The results of the application show that this game application can display 3D objects of the city of Parepare, which only focuses on the intersection area and around the Habibie Ainun True Love Monument area and is accompanied by an item search game.